Exciton–Polaron‐Induced Aggregation of Organic Electroluminescent Materials: A Major Degradation Mechanism in Wide‐Bandgap Phosphorescent and Fluorescent Organic Light‐Emitting Devices. Issue 7 (26th February 2015) - Wang, Qi; Aziz, Hany
<x xml:space="preserve">Abstract</x> The electroluminescence (EL) degradation mechanisms of organic light‐emitting devices (OLEDs) are studied utilizing phosphorescent and fluorescent materials as emitter guests. The results show that these emitter guests, despite being used in low concentrations in OLEDs, aggregate as a result of electrical stress, giving rise to the emergence of new longer‐wavelength bands in their EL spectra after prolonged device operation. Such electrical‐driving‐induced aggregation occurs more significantly in guest materials with wider bandgap (Eg) and flatter molecular structures. Further investigations reveal that the aggregation process is mainly induced by interactions between excitons and positive polarons that reside on the guests. The findings uncover a previously unknown degradation mechanism that appears to be responsible for the generally much lower EL stability of blue devices relative to their green and red counterparts, especially in case of phosphorescent emitters.